Role of IT in Business Expansion Possibilities of Family Owned Micro Food Products Business in Patiala - Neha; Singh, Gurcharan (Gyan Management Journal, 2017)
In the period of Globalization to expand business, every business need Information Technology solutions suited for special functions at different level of their organization to bring efficiency, raise market share and turn out to be competitive. This paper aims to understand the extent to which the family owned micro foods products companies in Patiala City of Punjab State uses IT Tools in business and find out the IT contribution in the expansion of Business. A Convenient sampling Technique has been used. The Five Family Managed Micro foods products companies out of ten based in Patiala city of Punjab has been taken. The primary data has been collected through questionnaire and interview method. To analyze primary data, Weighted Average Mean, Clustered Column Charts and Chi-Square Test of Goodness of fit have been used. The paper concludes that IT in respect of the family owned micro food product businesses in Patiala has played a vital role in business expansion and its possibilities but IT is not only the single factor responsible for such expansion and its possibilities. Information technology is a secondary tool in business expansion.